2020
DOI: 10.1111/1751-2980.12930
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae may serve as a probiotic in colorectal cancer by promoting cancer cell apoptosis

Abstract: Objectives: Shotgun metagenomic sequencing of human fecal samples has shown that Saccharomyces cerevisiae (S. cerevisiae) is significantly suppressed in colorectal cancer (CRC) and probably plays an important role in CRC progression. However, these results need to be validated. Here we aimed to confirm the results of highthroughput sequencing and demonstrate the mechanisms mediating the effect of S. cerevisiae on progression from colorectal adenoma (CRA) to CRC. Methods: We used a quantitative polymerase chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…boulardii . Results confirmed the presence of an enhanced percentage of apoptosis in probiotic yeast-treated cells [ 59 ].…”
Section: Clinical Significance Of S Cerevisiae Var...supporting
confidence: 63%
“…boulardii . Results confirmed the presence of an enhanced percentage of apoptosis in probiotic yeast-treated cells [ 59 ].…”
Section: Clinical Significance Of S Cerevisiae Var...supporting
confidence: 63%
“…In particular, Saccharomyces Cerevisiae YJM195 was positively associated with advanced pathological N-stage. However, evidence has shown that Saccharomyces Cerevisiae species have a tumor-suppressive role in colorectal cancer and are implicated in cell growth inhibition, B cell activation, and epithelial cell apoptosis [ 61 , 62 ]. Thus, further studies are required to elucidate the complex interactions and metabolism of Saccharomyces Cerevisiae within the HNSCC tumor microenvironment, which was negatively associated with patient prognosis in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CRC cell lines HCT116 and DLD1 treated for 4 h with S. cerevisiae , but not with its metabolites, showed an enhanced apoptosis rate. Taken together, these results indicate that S. cerevisiae may be involved in CRC progression, by acting on cell apoptosis [ 188 ]. Different probiotic strains, including S. boulardii (Unique-28), B. bifidum (UBBB-55), L. reuteri (UBLRu-87), L. plantarum (UBLP-40), L. fermentum (UBLF-31), L. salivarius (UBLS-22), Bacillus clausii (UBBC-07), Bacillus coagulans (Unique-IS2) and S. salivarius (UBSS-01), were put in contact with HCT116 cells for 24 h. Cancer cell apoptosis was induced again, confirming the possible use of selected probiotics as coadjutants for CRC [ 189 ].…”
Section: Olp Apoptotic Pathways and Probioticsmentioning
confidence: 94%